Rimpu Culture and the Existence of Bima Women: An Overview of Gender Perspectives - Yunus, Yunus; Amrin, Amrin; Sugiyarto, Sugiyarto; Supriyanto, Supriyanto (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2024)
The existence of rimpu in the Bima area has become a tradition, perception, and expression that indicates the awareness of women in cultivating local clothing without leaving the substance of Islamic teachings and carrying out their religious teachings. This research aims to examine the culture and existence of Bima women from a gender perspective. This research uses qualitative research with a literature study. The results show that the existence of rimpu for women is a means of expressing freedom for women by paying attention to theological and sociological values. Rimpu, which in the modern era has begun to erode and is in a dilemma with contemporary women’s styles, is less concerned about the cultural identity of their area. Therefore, rimpu is an encounter of Islamic teachings with local culture, requiring the involvement of all parties in preserving and caring for it as a local cultural identity